2013
DOI: 10.5392/jkca.2013.13.07.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotional Labor on the Burnout and Organizational Commitment among Flight Attendants

Abstract: The purpose of this study is to examine the relationship among the emotional labor, burnout, and organizational commitment in airline context. In this study, 2 hypotheses based on literature reviews were employed. Questionnaire was also developed based on previous studies. A convenience sample of 163 flight attendants was surveyed and 153 usable questionnaires were analyzed. According to the literature review, emotional labor was divided into 'surface acting' and 'deep acting'. Burnout, on the other hand, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Like studies in other service industries, studies on flight attendants' EE have been conducted and found negative relationships between flight attendants' EE and job-related outcomes such as job satisfaction (Ng et al 2011), job performance (Ko et al's 2013), turnover intention (Yoon and Yoon 2011), customer orientation (Shim and Jeong 2013), and organizational commitment (Ko 2013). It means that the more flight attendants become exhausted emotionally in their jobs, the less they are satisfied with their job or committed to their organization and customer service.…”
Section: Emotional Exhaustion (Ee)mentioning
confidence: 96%
See 1 more Smart Citation
“…Like studies in other service industries, studies on flight attendants' EE have been conducted and found negative relationships between flight attendants' EE and job-related outcomes such as job satisfaction (Ng et al 2011), job performance (Ko et al's 2013), turnover intention (Yoon and Yoon 2011), customer orientation (Shim and Jeong 2013), and organizational commitment (Ko 2013). It means that the more flight attendants become exhausted emotionally in their jobs, the less they are satisfied with their job or committed to their organization and customer service.…”
Section: Emotional Exhaustion (Ee)mentioning
confidence: 96%
“…Like EL studies in other service literature, studies on flight attendants' EL argued that flight attendants as ELs have to manage their actual emotions and display DA and SA according to job requirement set by the airlines (Ko 2013;Lee et al 2014). If flight attendants cannot manage their EL, they suffer more EE (Shim and Jeong 2013).…”
Section: Emotional Labor (El)mentioning
confidence: 97%
“…Many studies consistently show that surface acting more likely results in harmful well-being and health outcomes than deep acting (Lee et al, 2015). Ko (2013) found flight attendants have to manage their actual emotions and display deep acting if they cannot manage and regulate their emotions, and subsequently suffer more emotional exhaustion.…”
Section: Emotional Labourmentioning
confidence: 99%
“…Many studies consistently show that surface acting is more likely to result in harm to well-being and health outcomes than deep acting (Lee et al , 2015). According to Ko (2013), flight attendants have to manage their actual emotions and display deep acting, and if they cannot manage and regulate their emotions, they suffer more emotional exhaustion.…”
Section: Theoretical Reviewmentioning
confidence: 99%